Answered

Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

2x/3- y +7; x = 9, y=4


Sagot :

Answer:

-5

Step-by-step explanation:

2×9/3 - (4+7)

18/3 -11

18/3 - 33/3

-15/3

-5

Answer:

9

Step-by-step explanation:

2x/3- y +7; x = 9, y=4

plug in the numbers

2(9)/3-(4)+7

simplify 2(9)/3

2 • 9=18

18/3=6

6-4+7

6-4= 2

2+7=9